The Global Burden of Disease attributable to low physical activity and its trends from 1990 to 2019: An analysis of the Global Burden of Disease study - Xu, Yuan-Yi; Xie, Jin; Yin, Hao; Yang, Fang-Fang; Ma, Chun-Ming; Yang, Bao-Yi; Wan, Rui; Guo, Bin; Chen, Li-Dian; Li, Song-Lin (Frontiers in Public Health, 2022)
Introduction Low physical activity (LPA) is associated with several major non-communicable diseases (NCDs) and premature mortality. In this study, we aimed to assess the global burden and trends in disease attributable to LPA (DALPA) from 1990 to 2019. Methods Annual age-standardized disability-adjusted life years (DALYs) and death rates of DALPA [all-cause and five specific causes (ischaemic heart disease, diabetes mellitus, stroke, colon and rectal cancer, and breast cancer)] by sex, age, geographical region and social deprivation index (SDI) score from 1990 to 2019 were available from the Global Burden of Disease (GBD) study 2019. The estimated annual percentage changes (EAPCs) were calculated to quantify the changing trend. A generalized linear model (GLM) was used to explore the relationship between DALYs/death rates of DALPA and sociodemographic factors. Results Globally, in 2019, the age-standardized DALYs and death rates of DALPA were 198.42/100,000 (95% UI: 108.16/100,000–360.32/100,000) and 11.10/100,000 (95% UI: 5.66/100,000–19.51/100,000), respectively. There were 15.74 million (8.51–28.61) DALYs and 0.83 million (0.43–1.47) deaths attributable to LPA. Overall, age-standardized DALYs and death rates presented significant downward trends with EAPCs [−0.68% (95% CI: −0.85– −0.50%) for DALYs and −1.00% (95% CI: −1.13– −0.86%) for deaths] from 1990 to 2019. However, age-standardized DALYs and death rates of diabetes mellitus attributable to LPA were substantially increased [EAPC: 0.76% (95% CI: 0.70–0.82%) for DALYs and 0.33% (95% CI: 0.21–0.51%) for deaths]. In the 15–49 age group, DALPA presented significant upward trends [EAPC: 0.74% (95% CI: 0.58–0.91%) for DALYs and 0.31% (95% CI: 0.1–0.51%) for deaths]. The GLM revealed that higher gross domestic product and current health expenditure (% of GDP) were negatively associated with DALYs and death rates of DALPA. Conclusion Although global age-standardized DALYs and death rates of DALPA presented downward trends, they still cause a heavy burden worldwide. These rates showed upward trends in the diabetic and 15–49 age groups, which need more attention and health interventions.